Kinerja Keuangan Ditinjau Dari Leverage, Likuiditas, Ukuran Perusahaan, Dewan Komisaris Independen, Dan Komite Audit - Masna Rina Fitriyati; Kartika Hendra Titisari; Yuli Chomsatu Samrotun (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to examine and analyze the effect of leverage, liquidity, company size, independent board of commissioners and audit committee on financial perfomance. The data used in this study are secondary data ini the form of financial statements. The population in this study is LQ-45 companies listed on the Indonesia Stock Exchange in 2017-2019. Samples were selected from the purposive sampling method and 27 samples were obtained based on several criteria. The analysis technique used in this study is multiple linear regression analysis. The analysis shows that leverage, liquidity, independent commissioner influence of the financial perfomance.While the company size and audit committee has no effect on the financial perfomance. Simultaneously leverage, liquidity,company size, independent commissioner and audit committee were able to explain the dependent variable that is the financial perfomance by 54.3% and the rest was influenced by other variables. This research can be used by companies to increase the financial perfomance of the company.